Technology: a Challenge to exit the Risk? - Díaz Bernal, Juan Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article shows some transformations are experienced in the information age, in which methodological approach of phenomenological approach, analyzed and described and then discuss not only as technical devices and instrumental dimension but also examine their interrelationships as power and playback the capitalist system. In the first part, the relationship of concepts such as society, technology and culture evidence that life is based on the immediacy, immersion and speed of access in a technological world, bringing, multiple fractures that are here rethought from the educational perspective. In the background, entering the thematic discussion of the technologies in its context, namely, starting from the Fordism model to the conditions of teaching work linking higher education and technological innovation and the last part, it explains how to think and deal with technology taking advantage of their educational, cultural and political possibilities. In conclusion, the educational potential and technological objectives of the process is emphasized today.